PERAN PEMERINTAH DAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI KOTA MAGELANG (Studi Kasus pada Pelaksanaan Program “Rodanya Mas Bagia”) - Ristanto, Ristanto; Supardal, Supardal (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2024)
The success of development programs does not only rely on the role of government, but also involves the role of the community. Currently, society is placed as a subject in development. The government's role as a regulator and facilitator means that the government is obliged to prepare a set of rules as guidelines for implementing the program. The community is given the opportunity to be involved in planning, implementation and accountability. This research aims to determine the role of government and community participation in development in Magelang Municipality, especially in the implementation of the Rodanya Mas Bagia program. The research method used is descriptive qualitative using a case study approach. Data collection techniques used were interviews, observation and documentation. Secondary data is obtained from documentation, statutory regulations, books, journals or other publications. Data analysis is carried out through the process of data collection, data condensation, data presentation and drawing conclusions. The research results show that: 1) the planning stage, the community provides input, suggestions, ideas in the process of preparing the RT profile and preparing the community activity plan (RKM); 2) implementation stage, the community is involved to become members of the Pokmas. The spirit of mutual cooperation and community self-help grows in this program; and 3) at the results utilization stage, the benefits of procurement of goods such as procurement of CCTV, street lighting, construction of study halls, RW halls and RT facilities can be felt. The suggestions given by the researchers are that procurement of goods in the future will be directed at productive activities that are sustainable with community empowerment and the proposed activities can be based on regional communities in one RW, the capacity and competence of Pokmas still need to be increased so that they are not dependent on assistant staff, and there is a need to form Regional Regulations to further strengthen community empowerment policies.